The effects of dynamic compressive loading on human mesenchymal stem cell osteogenesis in the stiff layer of a bilayer hydrogel. (7th May 2019) - Aziz, Aaron H.; Eckstein, Kevin; Ferguson, Virginia L.; Bryant, Stephanie J.
Abstract: Bilayer hydrogels with a soft cartilage‐like layer and a stiff bone‐like layer embedded with human mesenchymal stem cells (hMSCs) are promising for osteochondral tissue engineering. The goals of this work were to evaluate the effects of dynamic compressive loading (2.5% applied strain, 1 Hz) on osteogenesis in the stiff layer and spatially map local mechanical responses (strain, stress, hydrostatic pressure, and fluid velocity). A bilayer hydrogel was fabricated from soft (24 kPa) and stiff (124 kPa) poly (ethylene glycol) hydrogels. With hMSCs embedded in the stiff layer, osteogenesis was delayed under loading evident by lower OSX and OPN expressions, alkaline phosphatase activity, and collagen content. At Day 28, mineral deposits were present throughout the stiff layer without loading but localized centrally and near the interface under loading. Local strains mapped by particle tracking showed substantial equivalent strain (~1.5%) transferring to the stiff layer. When hMSCs were cultured in stiff single‐layer hydrogels subjected to similar strains, mineralization was inhibited. Finite element analysis revealed that hydrostatic pressures ≥~600 Pa correlated to regions lacking mineralization in both hydrogels. Fluid velocities were low (~1–10 nm/s) in the hydrogels with no apparent correlation to mineralization. Mineralization was recovered by inhibiting ERK1/2, indicating cell‐mediated inhibition. These findings suggest that high strains (~1.5%) combined with higher hydrostatic pressures negatively impact osteogenesis, but in a manner that depends on the magnitude of each mechanical response. This work highlights the importance of local mechanical responses in mediating osteogenesis of hMSCs in bilayer hydrogels being studied for osteochondral tissue engineering.